Peran Sekolah Berbasis Pendidikan Islam dalam Pembentukan Karakter Religius di TK Nadwah Desa Tegalpanjang Kecamatan Cireunghas - Do`a Fajarwati; Siti Qomariyah; Nurasiah Jamil (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explore the Role of Islamic Education-Based Schools in the Formation of Religious Character in Nadwah Kindergarten focusing on the current large population in Indonesia and the rampant criminal acts and government programs through laws with the aim of research 1). describe the formation of religious character in Nadwah Kindergarten, 2). To describe the role of Islamic Education-Based Schools in the Formation of Religious Character in Nadwah Kindergarten 3). To describe the driving and inhibiting factors in the Formation of Religious Character in Nadwah Kindergarten. This study uses a qualitative approach with a descriptive method, qualitative research methods are also called naturalistic research methods because the research is conducted in very natural conditions (natural settings). Data collection through participatory observation, structured and unstructured interviews. documentation study using tools: observation guides, interview guidelines, data validation using Triangulation (sources), confirmability and dependability and analysis using reduction, data presentation and Drawing Conclusions The informants in this study were one Principal and two class teachers. The results of this study show 1). The formation of religious character in Nadwah Kindergarten has so far been running but has not been optimal through several habits that have been carried out, this is due to the different backgrounds of each family. Through the habit of saying hello to parents and teachers when saying goodbye and coming, then when entering the class, so far it has been going well. Dhuha prayer is performed once a month, but for memorizing the readings of obligatory prayers and ablution there is and memorizing short letters An-nas to At-takasur. 2). The role of Islamic education-based schools in the formation of religious character in kindergarten is very important because at this stage children are in a period of character formation that is very vulnerable and has a major influence on their development in the future. 3). these supporting and inhibiting factors and taking the necessary steps to strengthen children's character education. Collaboration between all stakeholders, including teachers, school staff, parents, and the community, is also important in building an environment that supports the formation of positive character for children in kindergarten.